The full radiostereometric analysis migration pattern of tibial components is associated with aseptic loosening: introducing MTPMemax (MTPM estimated maximum) - Bart G. Pijls; Elise K. Laende (Bone & Joint Research)
Aims: Thresholds for acceptable amounts of migration tibial components measured with radiostereometric analysis (RSA) are limited to specific follow-up moments and do not use the full migration pattern. The Michaelis-Menten (MM) model, a non-linear model from biochemistry, could potentially be used to model the entire migration pattern. The purpose of this study was therefore to determine if MM models can be fitted to RSA migration data of tibial components, and if these fitted model parameters can be used for early detection of tibial components at high risk for aseptic loosening. Methods: Migration patterns of tibial component maximum total point motion (MTPM) over six months, one year, and two years, as well as revision rates for aseptic loosening from previously published systematic reviews, were used. Fitted MM models gave the estimated maximal MTPM (MTPMemax) and a constant (K), which is the time in months at which half the MTPMemax is reached for tibial component designs. To assess model fit, intraclass correlation coefficients (ICCs) were calculated for the modelled MTPMemax and reported five-year MTPM values. The estimated MTPMemax and K-values were plotted against their corresponding five-year revision rate for aseptic loosening. Results: For six-month, one-year, and two-year migration patterns, the ICC was 0.81, 0.83, and 0.91, respectively, suggesting excellent agreement between calculated MTPMemax values and the known five-year MTPM values. MTPMemax up to 1.3 mm was considered to be safe based on association with aseptic loosening revision rate, while MTPMemax of more than 1.3 mm was unsafe. The K-value could not be used as a predictor for safe versus unsafe implants. Conclusion: MTPMemax values may be used for early detection of tibial components at high risk for aseptic loosening, possibly offering improvements over the older threshold system. Cite this article: Bone Joint Res 2025;14(5):398–406.